Self-Management and Knowledge Gaps in Chronic Disease Care: A Phenomenological Study of Patients with Hypertension, Diabetes Mellitus, and COPD in Indonesia - Inayati, Rahmi; Sofyan, Hizir; Tahlil, Teuku; Marthoenis, Marthoenis (Queeva Publishing, 2025)
Background: Non-communicable diseases (NCDs), including hypertension, diabetes mellitus, and chronic obstructive pulmonary disease (COPD), remain significant public health challenges in Indonesia. Despite advances in clinical management, patients lived experiences, particularly regarding disease-related knowledge and self-care practices, have received limited scholarly attention. Methods: A qualitative phenomenological approach was employed using focus group discussions and in-depth interviews with 19 participants, including 12 patients with hypertension, diabetes mellitus, and COPD; five primary health workers from community health center; and two district health office staff. The research was conducted between February and June 2024. Data were analyzed using descriptive phenomenological methods. Results: Three interrelated themes emerged. First, participants described delayed symptom recognition accompanied by limited initial understanding of their disease. Second, deeply entrenched lifestyle-related risk factors, including smoking, high salt and sugar intake, and physical inactivity. Third, inconsistent self-management practices following diagnosis. Although some participants attempted to adhere to medical advice and adopt healthier behaviors, these efforts were frequently constrained by inadequate health literacy, low motivation, and barriers to healthcare access. Persistent misconceptions regarding disease etiology were evident, reflected in culturally embedded terms such as “sweet urine” for diabetes and “lung pain” for COPD. Family support and religious beliefs were found to exert a dual influence, functioning as both facilitators and barriers to treatment adherence. Conclusion: Improving chronic disease outcomes in Indonesia requires the integration of culturally responsive health education, patient-centered communication, continuous follow-up, and health literacy interventions that are aligned with the sociocultural context of affected communities.